2019
DOI: 10.1093/jee/toz142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Appropriate Reference Genes For Investigating Gene Expression in Chlorops oryzae (Diptera: Chloropidae)

Abstract: Reverse transcription quantitative polymerase chain reaction (PCR) has become an invaluable technique for analyzing gene expression in many insects. However, this approach requires the use of stable reference genes to normalize the data. Chlorops oryzae causes significant economic damage to rice crops throughout Asia. The lack of suitable reference genes has hindered research on the molecular mechanisms underlying many physiological processes of this species. In this study, we used quantitative real-time PCR t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Thellin et al (1999) reported that at least two or more internal reference genes be combined to achieve accurate normalization because transcript levels of reference genes are not always stable and vary with the developmental stages and tissues of insects as well as under experimental conditions. For example, the expression of some reference genes, such as 18S , ACT , and GAPDH has been demonstrated to change broadly under particular experimental conditions. , Therefore, validation of candidate genes with stable expression levels as internal controls to normalize the expression of target genes is a prerequisite for RT-qPCR analyses. To date, studies on validation of suitable reference genes have been documented in some insect species, including Bactrocera dorsalis, Mythimna separate, , Helicoverpa armigera, and Bombyx mori .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thellin et al (1999) reported that at least two or more internal reference genes be combined to achieve accurate normalization because transcript levels of reference genes are not always stable and vary with the developmental stages and tissues of insects as well as under experimental conditions. For example, the expression of some reference genes, such as 18S , ACT , and GAPDH has been demonstrated to change broadly under particular experimental conditions. , Therefore, validation of candidate genes with stable expression levels as internal controls to normalize the expression of target genes is a prerequisite for RT-qPCR analyses. To date, studies on validation of suitable reference genes have been documented in some insect species, including Bactrocera dorsalis, Mythimna separate, , Helicoverpa armigera, and Bombyx mori .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the expression of some reference genes, such as 18S, ACT, and particular experimental conditions. 25,26 Therefore, validation of candidate genes with stable expression levels as internal controls to normalize the expression of target genes is a prerequisite for RT-qPCR analyses. To date, studies on validation of suitable reference genes have been documented in some insect species, including Bactrocera dorsalis, 27 Mythimna separate, 28,31 Helicoverpa armigera, 29 and Bombyx mori.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Freitas et al (2019) demonstrated that the ribosomal proteins RPL32 and RPS18 are the most stable reference genes in three stingless bee species despite developmental stage, sex, bacterial injection, or pesticide treatment. Other ribosomal proteins, such as the RPL13A gene of Thitarodes armoricanus , were the most stable under low‐temperature treatments (G. Q. Liu et al, 2016), and the RPS15 gene is the most stable gene expressed in different developmental stages and larval tissues of Chlorops oryzae (Tian et al, 2019). Similarly, our results also demonstrate the stability of ribosomal protein gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, in UV‐A treatment and different developmental stages, GAPDH gene expression is unstable. Tian et al (2019) showed that the GAPDH gene is unstably expressed in different developmental stages of C. oryzae . Similarly, the GAPDH gene is also the most unstable housekeeping gene under different treatments in three stingless bee species (Freitas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR was performed on a CFX96 Touch TM Real-Time PCR Detection System (Bio-Rad Laboratories, Hercules, CA, USA) in a reaction volume of 20 μl using TB Green TM Premix Ex Taq TM II (Takara), according to the manufacturer’s instructions. RPS15 ( ribosomal protein S15 ) and RP49 ( ribosomal protein 49 ) were the internal references genes 78 . A two-step program was performed as follows: 95 °C for 30 s, 40 cycles at 95 °C for 10 s and 59 °C for 30 s. A melting curve analysis was performed from 55 °C to 95 °C to determine the specificity of the qPCR primers and their efficiency was verified by calculating a standard curve (cDNA concentration vs. Ct) based on the dilution gradient of the templates.…”
Section: Methodsmentioning
confidence: 99%